2023
DOI: 10.3389/fendo.2023.1089298
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation alleviates insulin resistance in prediabetic rats by modifying IRS-1 and PPARγ/NF-κB expressions

Abstract: BackgroundPrediabetes is a condition of intermediate hyperglycemia that may progress to type 2 diabetes. Vitamin D deficiency has been frequently linked to insulin resistance and diabetes. The study aimed to investigate the role of D supplementation and its possible mechanism of action on insulin resistance in prediabetic rats.MethodThe study was conducted on 24 male Wistar rats that were randomly divided into 6 rats as healthy controls and 18 prediabetic rats. Prediabetic rats were induced with a high-fat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In terms of antiinflammation, PPARγ is expressed in both monocytes macrophages, which, after activation, inhibits monocytes or macrophages from producing inflammatory mediators IL-1β, IL-6, TNF-α, as well as inducible nitric oxide synthase [16]. PPARγ inhibits the proinflammatory gene expressions at the transcriptional level by antagonizing the activities of transcription factors like NF-κB, AP-1 and STAT1 [17], and its agonists can effectively inhibit the inflammatory molecule production mediated by microglia and astrocytes in the central nervous system [18,19]. GAS, as a small-molecule liposoluble monomer compound extracted from Rhizoma Gastrodiae with good druggability, has recently been approved as a therapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of antiinflammation, PPARγ is expressed in both monocytes macrophages, which, after activation, inhibits monocytes or macrophages from producing inflammatory mediators IL-1β, IL-6, TNF-α, as well as inducible nitric oxide synthase [16]. PPARγ inhibits the proinflammatory gene expressions at the transcriptional level by antagonizing the activities of transcription factors like NF-κB, AP-1 and STAT1 [17], and its agonists can effectively inhibit the inflammatory molecule production mediated by microglia and astrocytes in the central nervous system [18,19]. GAS, as a small-molecule liposoluble monomer compound extracted from Rhizoma Gastrodiae with good druggability, has recently been approved as a therapeutic drug.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in a subgroup of AMI patients (n = 123), in which vitamin D tests were available, levels of 25(OH)D were lower in T2D compared with non-T2D patients (mean:14 ± 8 vs. 22 ± 11 mg/dL, p ≤ 0.001), and the percentage of patients with 25(OH)D marked severe (< 10 mg/dL) was more than tripled in T2D compared with non-T2D patients (48% vs. 13%, p < 0.001). Moreover, other data suggested that the odds of having insulin resistance was significantly greater for subjects in the lowest quartile of 25(OH)D compared to the other quartiles combined, likely by modulation of several key pathways affecting glucose metabolism (e.g., increasing proinflammatory cytokines and oxidative stress affecting insulin signaling and epigenetic regulation of gene expression, as well as RAAS) [28][29][30][31]. It has been also suggested that low vitamin D is associated with atherogenic blood lipid profiles, whereas its supplementation is able to lower the levels of total cholesterol, triglycerides, and LDL cholesterol, as well as to increase HDL cholesterol [32].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of vitamin D on prediabetes present a contentious landscape in existing studies. Some studies suggest that VD supplementation during prediabetic stage with notably low VD levels improves insulin sensitivity, diminishes the risk of diabetes development, and improves insulin resistance in prediabetic rodents, while others have shown that treatment of VD 3 for 24 consecutive months does not improve OGTT-derived indices of β-cell function in prediabetic patients [1820] . Correspondingly, KKAy mice represent a spontaneously diabetic model characterized by hyperglycemia, impaired glucose tolerance, insulin resistance, and obesity induced by a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%